Effects of antenatal corticosteroids on neonatal blood glucose fluctuation in late-preterm infants - Zhou, Cailing; Zheng, Wanli; Zhang, Meixian; Tung, Tao-Hsin; Wang, Linghua; Wang, Lizhen (Frontiers in Pediatrics, 2022)
Objective: To evaluate the effects of antenatal corticosteroids (ACS) on blood glucose fluctuations in late-preterm infants. Methods: This was a retrospective study of 236 neonates at 34+0 to 36+6 weeks of gestational age who were admitted to the neonatology department of a tertiary general hospital in China’s Zhejiang Province between April 2020 and February 2022. The neonates were divided into three groups: complete course group, partial course group, and control group. Primary outcome was the neonatal blood glucose levels within the first 48 h of life. Results: 134 (56.8%) infants were exposed to a complete course of ACS, 56 (23.7%) had a to a partial course of ACS, and 46 (19.5%) had no exposure to ACS. The patients in the complete course group had the highest proportion of neonatal hypoglycemia (16.4% vs. 3.6% and 6.5%).The patients exposed to a complete course of dexamethasone had significantly lower blood glucose levels within 12 h of birth than the control group, although no significant differences were observed after 24 h. Differences in blood glucose levels were more significant among male infants, although blood glucose curves of the male and female infants remained close to the overall trend. Conclusions: Blood glucose levels in late-preterm neonates may decrease after ACS administration, especially after exposure to a complete course. The effects are more pronounced in the first 12 h of life, with males being more severely affected; however, the effects on blood glucose levels were not significant 24 h after birth. This can provide a reference for future clinical studies.